2020
DOI: 10.4317/jced.56331
|View full text |Cite
|
Sign up to set email alerts
|

A high salivary calcium concentration is a protective factor for caries development during orthodontic treatment

Abstract: Background: This research aimed to evaluate the salivary concentrations of fluoride (F -), calcium (Ca 2+ ), and phosphate (Pi) after brackets bonding, and to identify the role of [F -], [Ca 2+ ], and [Pi] on the development of active caries lesion (ACL) in individuals under fixed orthodontic treatment. Material and Methods: A longitudinal investigation with twenty-two individuals from 11 to 22 years of age was performed in four phases (baseline and after 1, 3, and 6 months). Analyses were carried out consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In growing patients undergoing fixed orthodontic treatment, Cardoso et al 17 showed that salivary composition plays an essential role in the development of active carious All patients experienced an increase in DMFT. The introduction of professional fluor prophylaxis did not cause significant changes in the increase of carious lesions.…”
Section: Influence Of Fixed Orthodontic Therapy On the Prevalence Of ...mentioning
confidence: 99%
“…In growing patients undergoing fixed orthodontic treatment, Cardoso et al 17 showed that salivary composition plays an essential role in the development of active carious All patients experienced an increase in DMFT. The introduction of professional fluor prophylaxis did not cause significant changes in the increase of carious lesions.…”
Section: Influence Of Fixed Orthodontic Therapy On the Prevalence Of ...mentioning
confidence: 99%
“…Moreover, it is also crucial to recreate the tooth mineral at the junction of the filling and tissue to seal the juncture and to prevent further erosion. Calcium-containing materials are characterized by satisfactory remineralization potential, , but the effectiveness of the process usually requires the simultaneous delivery of phosphate ions, which causes the precipitation of calcium phosphates. An inverse relationship between the concentration of calcium in dental plaque or saliva and the risk of caries was noticed. Therefore, providing calcium could result in anti-caries action. However, the main obstacle is related to the delivery of water-soluble bioavailable calcium, opening a floor for further investigation aimed at overcoming the limit . It is also claimed that some dental materials can have antibacterial effects originating from calcium contents. , …”
Section: Introductionmentioning
confidence: 99%
“…The natural source of calcium and phosphate is saliva, and research has shown that high saliva calcium levels are strongly correlated with low caries [ 16 , 17 ]. In contrast, agents like fluoride have to be provided from external sources, such as mouthwash, toothpastes or gums [ 18 ].…”
Section: Introductionmentioning
confidence: 99%